Ventricular Tachycardia in an Elderly Male With Brugada Syndrome - Mohammad Jaber MD; Sohaib Basharat MD; Rajagopal Krishnan MD; Shivang Shah MD; Richard Shu MD (SAGE Publishing, 2023)
We present a case of Brugada syndrome in a 74-year-old patient who presented with urine retention and incidentally found to have non-sustained ventricular tachycardia (NSVT) on electrocardiogram (ECG) and telemetry. To reveal characteristic type 1 Brugada pattern, right-pericardial lead was placed in the third right intercostal space. No antiarrhythmics were started, a loop recorder was implanted, and on follow-up episodes of self-terminating sustained ventricular tachycardia (VT) were noted. The patient was started on quinidine with resolution of VT.